2021
DOI: 10.3389/fimmu.2021.795580
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C-Reactive Protein in Dried Blood Spots and Saliva of Healthy Adolescents

Abstract: Background/AimDetermining C-reactive protein (CRP) by non-invasive methods is of great interest for research addressing inflammation in young people. However, direct comparisons of such methods applied in children and adolescents are lacking so far. This study aimed to evaluate the association between CRP measured in dried blood spots (DBS CRP) and in saliva (sCRP), two less invasive alternatives to venipuncture, in 12- to 14-year-old adolescents. To evaluate the validity of both measurements in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 55 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…Mixed data exist on equivalence of capillary blood, regarding liver 37 and kidney function tests 37 54 and complete blood count. 37 55 56 Promising results have been recently published regarding completely non-invasive measurement of CRP via saliva 57 or even continuously real time via a sweat-based wrist wearable. 58 In line with our results, previous studies could demonstrate that UA-based self-sampling is perceived as less painful compared with traditional venous blood collection 28 and finger pricking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed data exist on equivalence of capillary blood, regarding liver 37 and kidney function tests 37 54 and complete blood count. 37 55 56 Promising results have been recently published regarding completely non-invasive measurement of CRP via saliva 57 or even continuously real time via a sweat-based wrist wearable. 58 In line with our results, previous studies could demonstrate that UA-based self-sampling is perceived as less painful compared with traditional venous blood collection 28 and finger pricking.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed data exist on equivalence of capillary blood, regarding liver37 and kidney function tests37 54 and complete blood count 37 55 56. Promising results have been recently published regarding completely non-invasive measurement of CRP via saliva57 or even continuously real time via a sweat-based wrist wearable 58…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently demonstrated a positive correlation between salivary and serum hsCRP levels across various conditions, encompassing MI patients and controls. This suggests that saliva can be an alternative sample for assessing inflammatory markers such as hsCRP [ 5 ]. Saliva collection methods, including passive drool and swab-based techniques, offer standardized protocols for sampling and ease of use, rendering saliva a convenient and noninvasive sample for monitoring health status and detecting systemic disorders [ 5 , 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…This suggests that saliva can be an alternative sample for assessing inflammatory markers such as hsCRP [ 5 ]. Saliva collection methods, including passive drool and swab-based techniques, offer standardized protocols for sampling and ease of use, rendering saliva a convenient and noninvasive sample for monitoring health status and detecting systemic disorders [ 5 , 13 ]. The secretion of hsCRP in saliva is influenced by systemic inflammation and local oral factors.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation